“Relationship Marketing” trong giáo dục đại học ngoài công lập: Nghiên cứu trường hợp tại Trường Đại học Nguyễn Tất Thành - Nguyễn Thanh Phương , Nguyễn Thanh Phương (Tạp chí Giáo dục, 2024)
In the context of increasing competition in non-public higher education in Vietnam, understanding and managing the development of student loyalty has become critically important. This study approaches student loyalty and the quality of the student-private university relationship through the lens of relationship marketing theory. This theory emphasizes the importance of building and sustaining long-term relationships to enhance loyalty. In addition to a theoretical review, the study employs a qualitative methodology, including in-depth interviews with six students and a focus group discussion with fifteen students at a representative private university in Ho Chi Minh City. The findings indicate that the quality of the student-university relationship, primarily based on satisfaction, trust, and commitment, may serve as a key predictor of student loyalty. The research extends the application of relationship marketing theory within higher education and proposes future research directions to further enhance student loyalty, contributing to the field of educational marketing.